Until forever - Linn, Michael (Michael A.); Bailey, Stephen Anthony; Lawlor, Madison; Anderson, Jamie; Linn Productions; Soundview Media Partners ([Rapid City, SD] : Linn Productions, 2016)
High school sweethearts Michael and Michelle are madly in love with each other and dream about their future together. But when Michael is diagnosed with a rare cancer and confined to a hospital room, their love and faith are tested to the limits. Seeking answers to difficult questions, they begin praying for a miracle that does not seem to be coming. As Michael fights to live, his brother Matt struggles with his own illness: a dark and growing depression. And Michael's unlikely friendship with a fellow hospital patient provokes his own doubts about the value of life.
Originally released as a motion picture in 2016.
Stephen Anthony Bailey, Madison Lawlor, Jamie Anderson.
Cinematographer, Shaun O'Connell ; editors, Marc Linn, Michael Linn ; music, Christopher Roman.
In English.
Winner, Best Picture, International Christian Film Festival.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 30, 2020)
Keywords: Dating (Social customs) -- Drama; Teenagers -- Drama; Cancer -- Patients -- Drama; Depressed persons -- Drama; Christians -- Drama; Romance films; Fiction films; Christian films; Feature films; Internet videos; Streaming video